Crystal structure of N-(diaminomethylene)-1-(dimethylamino)-1-iminiomethanaminium dichloride, C4H13Cl2N5 - Xia Yu-Pei (Zeitschrift für Kristallographie - New Crystal Structures)
C4H13Cl2N5, monoclinic, P21 (no. 4), a = 7.1868(6) Å, b = 5.8408(4) Å, c = 12.6534(11) Å, β = 105.134(2)∘ $105.134{(2)}^{° }$ , V = 512.73(7) Å3, Z = 2, R gt(F) = 0.0354, wR ref(F 2) = 0.0961, T = 298 K.